Datix for Deaths Due to Physical Health Causes Outside Mental Health Inpatient Settings: Staff Perspective - Uchechukwu Egbuta; Manorama Bhattarai; Eimear Devlin (BJPsych Open)
Aims: Datix is a web-based incident reporting and risk management system used across hospitals in United Kingdom to report incidents. DATIX is used primarily for risk management. Therefore the purpose of reporting an incident is to alert the healthcare system to risks and to provide guidance on preventing potential incidents that may lead to avoidable harm or death. Datix can be used to report patient safety incidents or adverse incidents of varying categories such as unexpected effects, medication errors, etc. and these help to provide learning both at individual and organisational level.